2011
DOI: 10.1080/10934529.2011.598810
|View full text |Cite
|
Sign up to set email alerts
|

Human exposure to arsenic through foodstuffs cultivated using arsenic contaminated groundwater in areas of West Bengal, India

Abstract: The widespread incidence of chronic arsenicosis in the Bengal Delta has led to intensive research on arsenic (As) enrichment in groundwater as well as accumulation in foodstuffs, as there are potential health risks associated with exposure to As from both sources. This study deals with human As exposure through the drinking of groundwater, consumption of locally grown foodstuffs (e.g., crops and vegetables) and cooked food in Nadia district, West Bengal. Groundwater and foodstuffs were collected and analyzed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…Nine out of the total twenty districts of West Bengal have groundwater arsenic contamination [1,2]. Arsenic accumulation in rice straw argued to cause threat to cattle population and, thus contaminated meat and milk may indirectly cause further threat to humans, especially children [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Nine out of the total twenty districts of West Bengal have groundwater arsenic contamination [1,2]. Arsenic accumulation in rice straw argued to cause threat to cattle population and, thus contaminated meat and milk may indirectly cause further threat to humans, especially children [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The average arsenic concentration in the paddy fi eld soil of West Bengal was reported to be just below 10 mg kg −1 , the global average arsenic level in agricultural soil (Das et al 2002 ;Bhattacharya et al 2010a , b ;Samal et al 2011 ). The comparison of arsenic accumulation in grain of the six rice varieties in the present study at 10 mg kg −1 arsenic dosing showed that CNHR 3, a high yielding rice variety was the highest accumulator of arsenic (0.90 ± 0.15 mg kg −1 dry weight) while Nayanmani , a local rice variety was the lowest accumulator (0.48 ± 0.15 mg kg −1 dry weight).…”
Section: Resultsmentioning
confidence: 98%
“…Further the people having poor nutrition were found to be more vulnerable to As toxicity than the people having adequate nutrition (Santra et al 2013). Contamination of food chain and daily intake of As by human through food and drinking water was estimated in Nadia district where unsafe levels of the element in groundwater in widely prevalent (Samal et al 2011). Average concentrations of As in drinking water and commonly grown food in the area were 16 μg L À1 in drinking water, 156-194 μg kg À1 in rice, 69-780 μg kg À1 in vegetables and 24.7 μg kg À1 in pulse (lentil).…”
Section: Impact Of Fertilizer Use On Heavy Metal Build-up In Agricultmentioning
confidence: 99%